Human dental pulp stem cell responses to different dental pulp capping materials - Chawan Manaspon; Chavin Jongwannasiri; Sujin Chumprasert; Noppadol Sa-; Rangsini Mahanonda; Prasit Pavasant; Thantrira Porntaveetus; Thanaphum Osathanon (BMC, 2021)
Abstract Background Direct pulp capping is a vital pulp therapy for a pin-point dental pulp exposure. Applying a pulp capping material leads to the formation of a dentin bridge and protects pulp vitality. The aim of this study was to compare the effects of four dental materials, DyCal®, ProRoot® MTA, Biodentine™, and TheraCal™ LC in vitro. Methods Human dental pulp stem cells (hDPs) were isolated and characterized. Extraction medium was prepared from the different pulp capping materials. The hDP cytotoxicity, proliferation, and migration were examined. The odonto/osteogenic differentiation was determined by alkaline phosphatase, Von Kossa, and alizarin red s staining. Osteogenic marker gene expression was evaluated using real-time polymerase chain reaction. Results ProRoot® MTA and Biodentine™ generated less cytotoxicity than DyCal® and TheraCal™ LC, which were highly toxic. The hDPs proliferated when cultured with the ProRoot® MTA and Biodentine™ extraction media. The ProRoot® MTA and Biodentine™ extraction medium induced greater cell attachment and spreading. Moreover, the hDPs cultured in the ProRoot® MTA or Biodentine™ extraction medium migrated in a similar manner to those in serum-free medium, while a marked reduction in cell migration was observed in the cells cultured in DyCal® and TheraCal™ LC extraction media. Improved mineralization was detected in hDPs maintained in ProRoot® MTA or Biodentine™ extraction medium compared with those in serum-free medium. Conclusion This study demonstrates the favorable in vitro biocompatibility and bioactive properties of ProRoot® MTA and Biodentine™ on hDPs, suggesting their superior regenerative potential compared with DyCal® and TheraCal™.